2013
DOI: 10.5952/54-1-2-316
|View full text |Cite
|
Sign up to set email alerts
|

Water rituals as a source of (Christian) life in an African Independent Church: To be healed and (re)connected.

Abstract: 1Water rituals as a source of (Christian) life in an African Independent Church: To be healed and (re)connected ABSTRACT African Independent Churches (AICs) are to large extent paperless churches. This means that for the biggest part liturgical documents does not exist and that a study of their worship must entail a study of their enacted rites which will include recordings and transcriptions of verbal expressions such as sermons. This article focuses on AIC worship in South Africa, with special attention to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The important question is how the members experience these miracles and instances of healing. On the basis of this article, as well as other research papers produced in the context of the larger research project (Wepener 2009b(Wepener , 2013Wepener & Müller 2012;Wepener & Ter Haar 2013), it can be concluded that the life of the founder bishop Johannes Richmond is a prime example of the early phases of the invention of tradition within a context in which rapid changes have occurred and are occurring; but that the kind of group cohesion being fostered by this process is group cohesion, of which the core characteristic is cohesion aimed at the restoration of equilibrium in (South) African society. The Johannes Richmond who is currently being created is a Johannes Richmond whose life story assists members to cope with the changes they experience and helps them to survive in their communities as a group.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The important question is how the members experience these miracles and instances of healing. On the basis of this article, as well as other research papers produced in the context of the larger research project (Wepener 2009b(Wepener , 2013Wepener & Müller 2012;Wepener & Ter Haar 2013), it can be concluded that the life of the founder bishop Johannes Richmond is a prime example of the early phases of the invention of tradition within a context in which rapid changes have occurred and are occurring; but that the kind of group cohesion being fostered by this process is group cohesion, of which the core characteristic is cohesion aimed at the restoration of equilibrium in (South) African society. The Johannes Richmond who is currently being created is a Johannes Richmond whose life story assists members to cope with the changes they experience and helps them to survive in their communities as a group.…”
Section: Discussionmentioning
confidence: 96%
“…The group cohesion that this process fosters is in essence aimed at healing in all its multifaceted dimensions, which includes healing from physical ailments, 'healing' from barrenness, healing from spirit possession to healing as (re-)incorporation of an individual into the larger group (cf. Wepener & Müller 2012); the healing of a nation as well as healing from a dualistic spirit-matter worldview to a holistic worldview (Ter Haar 2009). One could say that what we find here is healing aimed at the restoration of equilibrium in African society, as John Mbiti (1999) puts it, but not only after the atrocities of apartheid, but also the restoration of equilibrium in the midst of the prevailing fracturing by many forces of a holistic worldview.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Ronald Grimes (2000:342; cf. also Wepener & Müller 2013) states: 'to be cured is to be fixed, to be healed is to be reconnected'.…”
Section: Introductionmentioning
confidence: 99%